The collected writings of John Maynard Keynes, Volume 16, Activities 1914-1919 : the Treasury and Versailles - Keynes, John Maynard 1883-1946 (Cambridge University Press for the Royal Economic Society, 2013)
From 1915, when Keynes joined the Treasury, until he resigned in 1919 during the Versailles Conference, he carried a rapidly increasing load of responsibility. This volume prints all the principal papers and memoranda he wrote during those years and throws new light on the crises of inter-allied financial relations and the near exhaustion of British financial resources. It contains also his contributions to the early thinking in the Treasury about post-war reparations and inter-allied debts. It ends with his correspondence, official and private, from Paris, as he saw his hopes of a wise settlement vanishing. This is a necessary companion to The Economic Consequences of the Peace (Volume 2 in this series)
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Versailles, Treaty of, June 28, 1919 (Germany); Weltkrieg (1914-1918); Wirtschaft; World War, 1914-1918 / Economic aspects; Großbritannien; Great Britain / Economic conditions